Design Of Semi Automatic Jominy Test For Metal Hardness Testing Practice - Irawan, Ibnu (International Journal of Science, Engineering, and Information Technology, 2024)
The design itself consists of various points of view called The Four C's of Design, namely: Creativity, Complexity, Choice, and Compromise. The Jominy Test tool is a tool for testing the hardenability of steel which is carried out by a cooling process (Quenching). The planning of the jominy test tool (Hardenability Jominy Test) is based on the ASTM A255 standard. Testing the semi-automatic jominy test tool on variations in valve openings against pressure height gets an average result, namely a valve opening angle of 15 ° as high as 0 mm, 30 ° as high as 5.3 mm, 45 ° as high as 27.3 mm, 60 ° as high as 48.3 mm, 75 ° as high as 62 mm, and 90 ° as high as 85 mm. This test shows that the greater the valve opening angle, the higher the water jet emitted. The height of the water jet has passed the desired standard of 63.5 mm, so that the valve angle reference can be taken between the angles of 75 ° and 90 °. The closest angle to the height of 63.5mm is 75° as high as 62mm, so to determine the height of 63.5mm to increase the angle. In the experiment conducted using angles of 76°, 77°, and 78°. The results obtained are at an angle of 76° as high as 63.5mm, 77° as high as 64°mm and 78° as high as 64.5°mm.